The Husbands-Wives Relation Model of Long Distance Marriage Farmer Households - Kismini, Elly; Wicaksono, Harto; Putri, Noviani Achmad (Universitas Negeri Semarang, 2018)
Somah orientation within family institutions shows that a father serves as the head of a family and a main worker of the family living together with his nuclear family has changed. The changes are not only in economic-social aspects, but also cultural aspects. The change occurs as a consequence of Long Distance Marriage (LDM) carried out by farmer families to meet their life needs. The study focused on the relationship model between husbands and wives in the farmer families whose husbands work in the city temporarily. The study shows that keeping husbands out of the village does not change much of the construction of patriarchal culture and the ideology of familialism in Tanggulangin community. The construction of the role of men and women in the LDM farmer families still exhibits the strong influence of patriarchal culture and familialism ideology that distinguishes the roles of men and women in the dichotomy of public and domestic roles as well as the patterns of senior-junior partner relations both at the theoretical and practical levels. Meanwhile, in the aspect of income earning and decision making, the relational model that is built in LDM farmer families LDM also depicts strong influence of patriarchy and ideologies familialism.